Gaya Hidup Urban Kalangan Mahasiswa di Kawasan Pasar Baru Kota Padang, 1992-2022 - Muhammad Isamuddin; Juanda Juanda; Yasmin Nazifah; Mila Azzahra (Medan Resource Center, 2022)
This study aims to see how the development in terms of boarding houses, clothing styles and transportation among Andalas University students in Pasar Baru. From this research it can be understood developments ranging from simple systems to sophisticated systems. The method used in this study used qualitative analysis which was obtained through interviews, field observations and reading sources related to this research. In this study there was a significant development due to the advancement of sophisticated science and technology. The lifestyle that used to be simple has become a modern and hedonic lifestyle. This lifestyle has also developed and become a culture among Andalas University students. From this description it is clear that students at Andalas University keep up with the times by following the flow and really enjoying the developments that exist among students.